ANALYSIS OF STOCK INTRINSIC VALUE USING RELATIVE VALUATION ON AGRICULTURE SECTOR LISTED IN JII70 PERIOD 2016-2019 - Dukalang, Hendra (Department of Islamic Banking, Faculty of Islamic Economics and Business, IAIN Sultan Amai Gorontalo, 2021)
This study aims to determine the intrinsic value or fair value of shares and the position of share value in Agriculture sub-sector companies, whether Overvalued (expensive), undervalued (cheap), or fair-valued (fair) using the relative valuation method approach for the 2016 – 2019 observation period in Agriculture sub-sector companies. The population in this study were 70 samples of companies from various sub-sectors. Determination of the sample is with the technique of purose sampling. So that the sample obtained is three companies in the field of agriculture with the provision that they have the most liquid index. Calculation data is processed using Ms. Excel 2010. The calculation results using the Relative Valuation Method are that AALI and LSIP companies are recommended for sale because they are in an Overvalued position, while SIMP company shares are recommended to be purchased because they are in an undervalued position